Preparation and Identification of New Azo ligand [(E)-3-((4,5-Diphenyl-1-Imidazole-2-yl) Diazenyl) Benzene Sulfonic Acid and Some of its Chelate Complexes - Obaid, , Nadia H. (International Journal of Psychosocial Rehabilitation, 2020)
This paper included preparation of ligand azo new which is derivative from 4,5-di phenyl imidazole. It also included the preparation of metal complexes for ions of Co(II), Ni(II),Cu(II),Zn(II),Cd(II) which is derivative from the new ligand. The ligand and metal complexes has been synthesized by FTIR, UV-Vis,1HNMR and mass spectrum, as the complexes have been synthesized by magnetic susceptibility. As result has proven that the prepared complexes have magnetic determination which are compatible with the octahedral shapes and the results of molar conductivity for the complexes that there is no ionic property for the complexes and based on these results. Octahedral shape has been suggested for all prepared complexes.